1993
DOI: 10.1016/0014-5793(93)80614-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ribosomal proteins by the vaccinia virus B1R protein kinase

Abstract: Two proteins of the 40s ribosomal subunit were shown to be phosphorylated m vitro by a vaccmia vnus-encoded sermelthreonine protein kinase. These were identified by two-dimensional gel electrophoresls as ribosomal protems Sa and S2 and were shown by phosphoamino acid analysis to both be phosphorylated on serme and threonine residues. The three phosphorylated forms of S2 produced by the BlR protein kinase m vitro matched the phosphorylated forms of S2 previously observed in cells infected with vaccmia virus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Therefore, these data strongly suggest that B1R plays an important role in the reduction of CD1d1-mediated antigen presentation following a VV infection. It has been shown that B1R phosphorylates one VVencoded and three host cell proteins [19,20]. The former is the product of the VV H5R gene product, a transcription factor expressed both early and late in the virus life cycle, and is involved in the transcription of VV late genes [14,21].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these data strongly suggest that B1R plays an important role in the reduction of CD1d1-mediated antigen presentation following a VV infection. It has been shown that B1R phosphorylates one VVencoded and three host cell proteins [19,20]. The former is the product of the VV H5R gene product, a transcription factor expressed both early and late in the virus life cycle, and is involved in the transcription of VV late genes [14,21].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the effects of B1 on BAF and H5, the viral kinase has been shown to phosphorylate two ribosomal proteins, Sa and S2, which may have consequences on the efficiency of viral versus cellular translation (13). In vitro kinase assays have shown that the A30 protein, which is involved in virion morphogenesis, may also be a B1 substrate (139).…”
Section: Poxvirusesmentioning
confidence: 99%
“…Also, it was impossible to generate a virus lacking the B1R open reading frame, which shows that it is an essential gene even without kinase activity (2), probably because of its ability to modulate other proteins by a direct interaction. So far, the identification of B1R substrates, either viral or cellular, is very limited; among its viral protein substrates is H5R (3), and among the cellular substrates are ribosomal proteins (1,4), BAF (30), and p53, which is hyperphosphorylated, triggering a downregulation of apoptotic signals (37) that could contribute to the survival of infected cells by transiently interfering with the cellular stress response and thus allowing the course of the infection to progress.…”
mentioning
confidence: 99%